Frequency of Hyperprolactinemia and Its Associations With Demographic and Clinical Characteristics and Antipsychotic Medications in Psychiatric Inpatients in China. Issue 4 (20th November 2013) - Wang, Zhi‐Min; Xiang, Yu‐Tao; An, Feng‐Rong; Correll, Christoph U.; Ungvari, Gabor S.; Wang, Chuan‐Yue; Lai, Kelly Y. C.; Bo, Qi‐Jing; Li, Yan; Zhong, Bao‐Liang; Chiu, Helen F. K.
<x xml:space="preserve">Abstract</x> Purpose No study has investigated hyperprolactinemia and its risk factors in Chinese psychiatric patients. This study examined the prevalence of hyperprolactinemia and its relationship with demographic and clinical characteristics in inpatients in a large psychiatric institution in Beijing, China. Design and Methods A consecutive sample of 617 psychiatric inpatients formed the study sample. Basic sociodemographic and clinical data including serum prolactin level were collected. Findings The prevalence of hyperprolactinemia was 55.9% in the whole sample, and 56.8% and 43.2% for women and men, respectively. The corresponding figures were 59.6%, 40.0%, 53.6%, and 50.8% in schizophrenia spectrum disorders, major depression, bipolar disorders, and other psychiatric disorders, respectively (p = 0.09). In univariate analyses, patients having hyperprolactinemia were younger, more likely to receive risperidone, amisulpride, and first‐generation antipsychotics, but less likely to receive clozapine and aripiprazole. In multiple logistic regression analysis, hyperprolactinemia was independently associated with younger age, more use of risperidone or amisulpride and first‐generation antipsychotics, and less use of clozapine and aripiprazole (r2 = 0.197). Practice Implications Hyperprolactinemia is very common in Chinese psychiatric inpatients. Given the potentially harmful consequences of hyperprolactinemia and its preventable nature, effective measures to lower the frequency hyperprolactinemia in patients with major psychiatric disorders should be implemented in Chinese mental health facilities.